The evaluation method for distance learning engagement of college English under the mixed teaching mode. (24th March 2022) - Zhang, Yansong; Yang, Yanbin
In order to overcome the problems of low input and poor effectiveness of evaluation, this paper puts forward the evaluation method of distance learning input. This method constructs a learning behaviour input model under the mixed teaching mode of college English. We determine the evaluation standard of learning engagement as the comparison standard of evaluation indicators, collect the learning information of students in the process of distance English learning, and determine the specific indicators of learning input evaluation. Combined with the weight of the index, the specific value of the comprehensive evaluation index of learning input is calculated, and the final evaluation result of learning input is obtained by comparing with the evaluation standard. The experimental results show that the evaluation results are all over 85%, the evaluation effectiveness is 90%, and the average English score is improved by 7.8 points.